Effects of Using Inulin and Grape Pomace in Broiler Diets on Performance, Carcass Yield, Intestinal Viscosity, Immunity, and Antioxidant Status - Şen, G; Başalan, M (Journal of the Hellenic Veterinary Medical Society, 2022)
This study was carried out to investigate the effects of inulin and grape pomace addition to broiler diets on performance, carcass yield, intestinal viscosity, immunity, and antioxidant status. In the study, a total of 160 unsexed 0-day-old Ross 308 broiler chicks were divided into 4 groups as follows: the control (CON) group, and the groups consuming diets with 10 g/kg inulin (IN), 50 g/kg grape pomace (GP), and 10 g/kg inulin + 50 g/kg grape pomace (INGP) respectively. At the end of the experiment which lasted 42 days, 48 animals were bled for the analysis of immunity and antioxidant parameters. At the end of the study period, while body weight gain, carcass yield and intestinal viscosity values between the groups was not significant, grape pomace had a negative effect on feed consumption and feed conversion ratios (P<0.05). Immunoglobuline (Ig) G levels of the animals in the INGP group were significantly lower than those - in the other groups (P<0.05). The Catalase (CAT) activity was increased in groups consumed diets containing grape pomace (P<0.05). While β carotene level was elevated by inulin in the blood of animals, vitamin C and E levels were elevated by inulin and grape pomace significantly (P<0.05). As a result, it was observed that the use of inulin and grape pomace in broiler diets had no negative effect on carcass yield, intestinal viscosity, and antioxidant status. However, the inulin and grape pomace combination on feed cosumption, feed efficiency and immunity had a negative effect.